Slow magnetic relaxation in mononuclear octa-coordinate Fe(ii) and Co(ii) complexes from a Bpybox ligand. Issue 22 (30th May 2022) - Li, Rui-Xia; Sun, Hui-Ying; Liang, Hai-Chao; Yi, Cheng; Yao, Nian-Tao; Meng, Yin-Shan; Xiong, Jin; Liu, Tao; Zhu, Yuan-Yuan
Abstract : Two mononuclear octa-coordinate Fe(ii ) and Co(ii ) complexes display field-induced slow magnetic relaxation in which Fe(ii ) and Co(ii ) compounds are uniaxially and rhombically anisotropic, respectively. Abstract : Two 3d transition metal mononuclear complexes, [(Fe L 2 )(ClO4 )2 ]2 ·CH3 CN (1 ) and (Co L 2 )(ClO4 )2 ·2CH3 CN (2 ), have been prepared from a rigid tetradentate bpybox ( L = 6, 6′-bis(2, 5-dihydrooxazol-4-yl)-2, 2′-bipyridine) ligand. Single crystal X-ray diffraction analyses together with the help of calculations show that both compounds are octa-coordinate. Direct current magnetic studies reveal their significant magnetic anisotropy. Impressively, field-induced relaxation of magnetism is observed in the two complexes and the apparent anisotropy barriers are 14.1 K for 1 and 21.6 K for 2, respectively. Theoretical calculations reveal that two Fe(ii ) centers in 1 have small negative D values of −4.897 and −4.825 cm −1 and relatively small E values of 0.646 and 0.830 cm −1, indicating a uniaxial magnetic anisotropy. In contrast, the D and E values in the Co(ii ) center of 2 are 46.42 cm −1 and 11.51 cm −1, featuring a rhombic anisotropy. This work demonstrates that field-induced slow magnetic relaxation in 3d transition metal complexes with high coordination numbers can be manipulated through rigid ligand design.